Introduction to food science and technology - Stewart, George Franklin (Academic Press, 1973)
The Second Edition of this popular textbook has benefited from several years of exposure to both teachers and students. Based on their own experiences as well as those of others, the authors have reorganized, added, and updated this work to meet the needs of the current curriculum. As with the first edition the goal is to introduce the beginning student to the field of food science and technology. Thus, the book discusses briefly the complex of basic sciences fundamental to food processing and preservation as well as the application of these sciences to the technology of providing the consumer with food products that are at once appealing to the eye, pleasing to the palate, and nutritious to the human organism. Introduction to Food Science and Technology is set in the world in which it operates; it contains discussions of historical development, the current world food situation, the safety regulations and laws that circumscribe the field, and the careers that it offers